2018
DOI: 10.1007/s00248-018-1228-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Antimicrobial Resistance Traits of Commensal Human Gut Microbiota

Abstract: Antimicrobial resistance (AMR) among bacterial species that resides in complex ecosystems is a natural phenomenon. Indiscriminate use of antimicrobials in healthcare, livestock, and agriculture provides an evolutionary advantage to the resistant variants to dominate the ecosystem. Ascendency of resistant variants threatens the efficacy of most, if not all, of the antimicrobial drugs commonly used to prevent and/or cure microbial infections. Resistant phenotype is very common in enteric bacteria. The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…Functional Evaluation of Resistance Traits. Several in silico studies have revealed a plethora of commensals, symbionts, and opportunistic pathogens inhabiting the human gastrointestinal tract housing hundreds of AMR genes in their genomes (10,13). The functions of AMR genes were predicted by comparing sequence homology to the genes that have been cataloged as AMR genes in the databases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional Evaluation of Resistance Traits. Several in silico studies have revealed a plethora of commensals, symbionts, and opportunistic pathogens inhabiting the human gastrointestinal tract housing hundreds of AMR genes in their genomes (10,13). The functions of AMR genes were predicted by comparing sequence homology to the genes that have been cataloged as AMR genes in the databases.…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanisms such as efflux pumps, reduced permeability, alternative metabolic pathways, target modifications, enzymatic inactivation of antimicrobials, and so forth can confer antibiotic resistance in bacterial species (8). Many of the antibiotic resistance genes are physically linked with mobile genetic elements (MGEs) and disseminate to closely or distantly related bacterial species by lateral and vertical gene transfer (9,10). The genes that encode resistance function and the genetic elements that carry the resistance genes widely vary depending upon the type of pathogen and their geographic locations (11).…”
mentioning
confidence: 99%
“…is an early intestinal colonizer and commensal which impacts the development of newborns in multiple beneficial ways and have been developed as probiotics for the prevention and treatment of diseases (25). Recent work by Bag et al (26) and Duranti et al (27) demonstrated the existence of ARGs in whole-genome sequence (WGS) of Bifidobacteria sp. Bag et al showed the physical linkage of these ARGs against different classes of antimicrobials to MGEs in the WGS of a strain of Bifidobacterium longum indica that was isolated from feces of a healthy Indian adult (26).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Bag et al (26) and Duranti et al (27) demonstrated the existence of ARGs in whole-genome sequence (WGS) of Bifidobacteria sp. Bag et al showed the physical linkage of these ARGs against different classes of antimicrobials to MGEs in the WGS of a strain of Bifidobacterium longum indica that was isolated from feces of a healthy Indian adult (26). Duranti et al found interspecies variation in breakpoint levels for antibiotics like streptomycin and tetracycline indicating the role of HGT in the evolution of AMR in Bifidobacteria sp.…”
Section: Discussionmentioning
confidence: 99%
“…Separate studies have proven that the genes for antibiotic tolerance may be exchanged horizontally among Bacteroides or between Bacteroides and Gram-positive bacteria (Husain et al 2017) and inherited as well (Vaishampayan et al 2010). The gut microbiota contains a set of antibiotic resistance genes especially against b-lactam, glycopeptides, tetracycline and aminoglycosides (Bag et al 2019). Recently, it has been shown that gut microbes transform the active drugs into inactive metabolites as done by species of Firmicutes and Enterococcus faecalis (Lam et al 2019).…”
Section: Antibiotic Stress Tolerance Mechanismmentioning
confidence: 99%